Three Faces of Populism in Current Switzerland: Comparing the Populist Communication of the Swiss People's Party, the Ticino League, and the Geneva Citizens' Movement. Issue 4 (31st October 2017) - Bernhard, Laurent
Abstract: This article breaks new ground by comparatively analyzing the populist communication of the three major radical right parties of current Switzerland – the Swiss People's Party (SVP), the Ticino League (Lega), and the Geneva Citizens Movement (MCG). Based on a quantitative analysis of party newspaper articles published from 2009 to 2015, this study finds that 1) the three parties exhibit higher levels of populist communication than mainstream parties, 2) that the populist communication of both the Lega and the MCG does not vary across issue domains, while the SVP significantly relies more on cultural populism than on economic populism, and 3) that the strong oppositional figures (i.e. Christoph Blocher for the SVP, Giuliano Bignasca for the Lega, and Eric Stauffer for the MCG) more frequently play the populist card than the remaining party members.